2009
DOI: 10.1128/jb.00708-09
|View full text |Cite
|
Sign up to set email alerts
|

PhoB Regulates Motility, Biofilms, and Cyclic di-GMP inVibrio cholerae

Abstract: Signaling through the second messenger cyclic di-GMP (c-di-GMP) is central to the life cycle of Vibrio cholerae. However, relatively little is known about the signaling mechanism, including the specific external stimuli that regulate c-di-GMP concentration. Here, we show that the phosphate responsive regulator PhoB regulates an operon, acgAB, which encodes c-di-GMP metabolic enzymes. We show that induction of acgAB by PhoB positively regulates V. cholerae motility in vitro and that PhoB regulates expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 57 publications
4
73
0
2
Order By: Relevance
“…The shaded region represents the mean level of WT or ⌬cdgJ Ϯ standard deviations. (5,7,33,42). We showed that CdgJ inversely regulates motility and biofilm formation and functions as a PDE.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The shaded region represents the mean level of WT or ⌬cdgJ Ϯ standard deviations. (5,7,33,42). We showed that CdgJ inversely regulates motility and biofilm formation and functions as a PDE.…”
Section: Discussionmentioning
confidence: 97%
“…Motility and chemotaxis genes are upregulated in the rabbit ileal loop during detachment, a process termed mucosal escape response (37). It also has been shown that some of the genes encoding c-di-GMP-metabolizing enzymes are induced during the late infection stage and help bacteria to become motile and prepare for the aquatic life cycle (42,49,55). A better understanding of the molecular mechanisms involved in c-di-GMP-regulated motility therefore is critical for understanding the pathogenesis and environmental survival of V. cholerae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it was shown that PhoB negatively affects CT and TCP expression by repressing the tcpPH promoter (Pratt et al, 2010). In addition, PhoB negatively regulates biofilm formation in V. cholerae of classical and El Tor biotypes (Pratt et al, 2009;Sultan et al, 2010). A comparison of the levels of expression of known regulators of vps and biofilm between wild-type and phoB V. cholerae of the El Tor biotype revealed that VpsR, is negatively regulated by PhoB (Sultan et al, 2010).…”
Section: Effect Of Extracellular Phosphate On Vps Expression and Biofmentioning
confidence: 99%